EFFICACY AND SAFETY OF LUBRICATING JELLY INSTILLATION TO PREVENT RETROPULSION DURING URETEROLITHOTRIPSY FOR URETERAL STONES - Yuanda, Rameshdo; Soebadi, Doddy M; Soetojo, Soetojo; Hardjowijoto, Sunaryo (Indonesian Journal of Urology, 2017)
Objective: We studied the efficacy and safety of lubricating jelly instillation before ureterolithotripsy for prevention of retropulsion and improvement in stone-free rate. Material & methods: We enrolled 22 subjects with ureteral stone in this prospective, randomized, single-blind and controlled clinical trial. Each subject was randomly assigned to the lubricating jelly instillation group (n=11) and control group (n=11). Ureteroscopy and lithotripsy was performed according the standard protocol, using 9.8 F semirigid ureteroscope and pneumatic lithotripter. A 6 F ureteral catheter was advanced beyond the stone, and lubricating jelly was instilled through the catheter lumen. Retropulsion and the presence of residual fragments were evaluated with plain kidneys, ureters and bladder x-ray and ultrasonography, or Non Contrast-enhanced Computed Tomography. Any complication was reported and graded using the Modified Clavien Classification System.Results: The 2 groups had comparable preoperative characteristics. There were no statistically significant difference between the lubricating jelly instillation group and control group regarding the retropulsion rate (54.5% vs 72.7%, ρ=0.375), the stone-free rate (54.5% vs 36.4%, ρ=0.392), and the complication rate (45.5% vs 54.5%, ρ=0.670). Conclusion: Lubricating jelly instillation during ureterolithotripsy has limited value for prevention of retropulsion and improvement in stone-free rate.